A system science perspective of the drivers of equatorial plasma bubbles - Klenzing, Jeff; Halford, Alexa J.; Liu, Guiping; Smith, Jonathon M.; Zhang, Yongliang; Zawdie, Kate; Maruyama, Naomi; Pfaff, Rob; Bishop, Rebecca L. (Frontiers in Astronomy and Space Sciences, 2023)
The complex drivers of equatorial plasma bubbles and resulting scintillation requires a system science approach spanning the Magnetosphere-Ionosphere-Thermosphere-Mesosphere disciplines. The current roadmap missions strongly support this approach, but gaps are identified in planned observations, with potential mission and solutions proposed.